2019
DOI: 10.3389/fphar.2019.01262
|View full text |Cite
|
Sign up to set email alerts
|

Surprising Anticancer Activities of Psychiatric Medications: Old Drugs Offer New Hope for Patients With Brain Cancer

Abstract: Despite decades of research and major efforts, malignant brain tumors remain among the deadliest of all cancers. Recently, an increasing number of psychiatric drugs has been proven to possess suppressing activities against brain tumors, and rapid progress has been made in understanding the potential mechanisms of action of these drugs. In particular, the traditional mood stabilizer valproic acid, the widely used antidepressants fluoxetine and escitalopram oxalate, and the atypical psychiatric drug aripiprazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…Interestingly, our results suggest that some conventional antipsychotics among drugs mentioned above, including amitriptyline, fluoxetine, and imipramine, may also play a surprising role in the treatment of GBM, which is consistent with previous studies and offers new hope for patients with GBM (12,75,76,80,83,84,104). In addition, Leite et al (105) demonstrated that clomipramine (tricyclic antidepressant drugs such as imipramine) has an impact on GBM growth and has no toxicity in normal cells (astrocytes and microglia).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, our results suggest that some conventional antipsychotics among drugs mentioned above, including amitriptyline, fluoxetine, and imipramine, may also play a surprising role in the treatment of GBM, which is consistent with previous studies and offers new hope for patients with GBM (12,75,76,80,83,84,104). In addition, Leite et al (105) demonstrated that clomipramine (tricyclic antidepressant drugs such as imipramine) has an impact on GBM growth and has no toxicity in normal cells (astrocytes and microglia).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we used CMap analysis to accurately identify compounds that have been shown to have specific effects on GBM or other tumor types by comparing the different expression genes of GMB samples from 3 clusters. These compounds include the DNA synthesis inhibitor anisomycin ( 73 ), glutamate receptor antagonist amantadine ( 74 ), norepinephrine inhibitor amitriptyline ( 75 , 76 ), solute carrier family member inhibitor bumetanide ( 77 ), PPAR receptor agonist clofibrate ( 78 ), and fenofibrate ( 79 ), selective serotonin reuptake inhibitor (SSRI) fluoxetine ( 75 , 80 ), ATPase inhibitor helveticoside ( 81 , 82 ), norepinephrine reuptake inhibitor imipramine ( 75 , 76 , 83 , 84 ), opioid receptor agonist loperamide ( 85 ), phosphodiesterase inhibitor papaverine ( 86 , 87 ) and rolipram ( 88 92 ), polar auxin transport inhibitor quercetin ( 93 , 94 ), cyclooxygenase inhibitor rofecoxib ( 95 , 96 ), calcineurin inhibitor tacrolimus ( 97 ), purinergic receptor antagonist ticlopidine ( 98 , 99 ), HDAC inhibitor vorinostat ( 100 ), Rho associated kinase inhibitor Y-27632 ( 101 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychotropic drugs are revealing promising candidates for drug repositioning in cancer. Although several in vitro and in vivo models reported the efficacy of this family of drugs in reducing cancer cell viability and tumor growth (30,32,62), the pharmacological properties underpinning the possible clinical application of psychotropic drugs for cancer therapy remain poorly understood. In this study we investigated a large panel of psychotropic drugs for their potential antitumoral activity evaluating their cytotoxic effect in six cell lines derived from three different tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have repeatedly reported that individuals who are receiving long term drug treatment with antipsychotics (24,25), anti-depressant (26)(27)(28) or anti-allergic drugs (29) have a lower cancer incidence than the general population, suggesting that these medications might have a direct effect on neoplastic cells. Pre-clinical studies confirmed the direct anti-tumoral activity of these compounds in a wide range of malignancies (30)(31)(32)(33)(34). However, despite the large body of experimental evidence, the mechanisms of actions of these compounds in cancer cells remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant in vitro evidence on radiosensitizing effects of VPA on many different tumor cell lines; this leads to the assumption that adding VPA would lead to improved tumor control by making cancer cells particularly susceptible to irradiation, overcoming potential radioresistance and thus better outcomes. Despite promising preclinical results, however, evidence for clinical benefit of VPA in oncological treatment remains controversially discussed [ 15 , 42 44 ]. We hypothesize that patients taking VPA might have an increased risk to suffer from radiation induced side effects due to their increased radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%